A Review On: Substance Abuse - Soni, Shwetansh; Sharma, Archana; Khinchi, M. P; Gauttam, Narendra; Gauttam, Shubham (Asian Journal of Pharmaceutical Research and Development, 2017)
Drug Abuse- The focus of this article is to review the recent advances in preventing the misuse of the Controlled Substance like Barbiturates, Benzodiazepines, Cannabis, Cocaine, Methaquolone, Opioids & Alcohol. This Prevention of the Substance Abuse can be understood on the basis of the data provided in article by means of Dual Diagnosis, Signs & Symptoms which enlists the populations that are highly affected and are on a verge of addiction to the drugs. Effect of Substance Abuse on countries overall economy, Legal approaches taken by the various governments, diagnosis of addiction, treatment and side effects are also the areas covered in this article.